2009
DOI: 10.1590/s1982-56762009000300006
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of calcium chloride and calcium silicate decreases white mold intensity on dry beans

Abstract: White mold (Sclerotinia sclerotiorum) is the most important common bean disease during the fall-winter season in Brazil. Different control strategies are necessary to control this disease and increase bean yield in infested areas. The aim of this research was to evaluate the effect of application of calcium chloride (CaCl 2 ) and calcium silicate (CaSiO 3 ) on white mold control on common bean. The experiment was carried out during the 2006 fall-winter season in Viçosa MG, Brazil, in a field naturally infested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Previous research results have also confirmed the role of calcium in inducing disease resistance. For instance, studies by Paula Júnior et al have shown that spraying CaCl 2 and CaSiO 3 on bean leaves significantly reduces the disease index of bean plants infected with Sclerotinia sclerotiorum [ 44 ]; Yoon et al found that treatments with different calcium compounds significantly reduce the susceptibility of peppers to Botrytis cinerea [ 45 ]. Thus, the use of calcium as an elicitor for controlling peanut diseases holds broad prospects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research results have also confirmed the role of calcium in inducing disease resistance. For instance, studies by Paula Júnior et al have shown that spraying CaCl 2 and CaSiO 3 on bean leaves significantly reduces the disease index of bean plants infected with Sclerotinia sclerotiorum [ 44 ]; Yoon et al found that treatments with different calcium compounds significantly reduce the susceptibility of peppers to Botrytis cinerea [ 45 ]. Thus, the use of calcium as an elicitor for controlling peanut diseases holds broad prospects.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium silicate inhibited conidial germination and mycelial growth of Fusarium sulphureum in controlled dry rot of potato tubers (Li et al, 2009). Calcium silicate reduced downy mildew (Peronospora manshurica) in soybean (Nolla et al, 2006), and when applied with calcium chloride, white mold (Sclerotinia sclerotiorum) in dry beans (Paula Júnior et al, 2009). Foliar application of silicates might act as a physical barrier to pathogen infection, but root application of potassium metasilicate increased plant defenses and controlled downy mildew (P. xanthii) in cucumber (Liang et al, 2005).…”
Section: Silicates and Phosphitesmentioning
confidence: 99%
“…In bean, disease incidence and severity of white mould (Sclerotinia sclerotiorum) were significantly reduced by 52% and 73%, respectively, via applying Si as calcium silicate together with calcium chloride (PaulaJúnior et al, 2009).…”
Section: White Mouldmentioning
confidence: 99%